Quantitative determination of 4-((5-(decylthio)-4-methyl-4-h-1,2,4-triazol-3-yl)methyl)morpholine in the soft medicinal form by spectrophotometric method - K. V. Khomenko; K. P. Medvedevа; I. V. Bushueva; S. A. Vasyuk; Zh. M. Polova (The State Expert Center of the Ministry of Health of Ukraine, 2023)
Synthetic biologically active compounds are the active pharmaceutical ingredients of various dosage forms that are widely used in both human and veterinary medicine. Nowadays the development of new effective antimicrobial and antifungal drugs remains a actual problem. This fact has a reasoned explanation in connection with the increase in infectious diseases of microbial and fungal etiology and the ever-growing resistance of microorganisms and fungi to various drugs. The aim of this research was to develop and validate a new spectrophotometric method for the quantitative determination of 4-((5-(decylthio)-4-methyl-4-H-1,2,4-triazol-3-yl)methyl)morpholine in 7% ointment by intrinsic absorption. At the stage of development of the quantitative determination method, the solvent was selected based on the solubility of the active substance. According to the data provided, 4-((5-(decylthio)-4-methyl-4-H-1,2,4-triazol-3-yl)methyl)morpholine is insoluble in water, but soluble in ethanol, methanol, isopropanol, dioxane, and dimethyl sulfoxide. Ethanol was chosen as the most accessible and less toxic solvent for the development of this method. Studied 4-((5-(decylthio)-4-methyl-4-H-1,2,4-triazol-3-yl)methyl)morpholine dissolved in ethanol is introduced into the ointment base as a solution. The quantitative content of substances subject to chemical control in soft dosage forms should be between 90% and 110% of the nominal content. On this basis, the maximum permitted analytical uncertainty can be determined, which is 3.20. During the procedure the main validation characteristics were determined, such as: linearity, precision, accuracy and robustness. Thus, a new sensitive, economical and easy-to-use spectrophotometric method for the quantitative determination of 4-((5-(decylthio)-4-methyl-4-H-1,2,4-triazol-3-yl)methyl)morpholine in a soft dosage form for external use (7% ointment) by the intrinsic absorption method was developed. According to the main validation characteristics (linearity, precision, accuracy and robustness), the proposed method is valid and meets the requirements of the State Pharmacopoeia of Ukraine.